What is the “reflexive historicizing of communication”? A philosophical approach - Wendland, Michał (Lingua Posnaniensis, 2017)
The purpose of this article is to interpret the term the “reflexive historicizing of communication” used by the editors of the Handbook of Communication History published in 2013. In the preface and in the first chapter, the editors introduce the above-mentioned concept, postulating that it is associated with the most important among several possible trends in communication history. Reflexive historicizing, as an important and innovative methodological directive, however, is described therein rather laconically. This article contains comments on both historicism and reflexivity. Their genesis is presented as well as their most important interpretations and possible applications in the social sciences. Particular attention is paid to the concept of historicism, since it is charged with numerous controversies and polemics (Karl Popper’s famous criticism). The main purpose of this article is to explain the meaning of historicism (and reflexivity) so as to avoid confusion and over-interpretation in the application of these concepts within communication history.